Consumer Acceptance of V60-Brewed Pupuan Robusta Coffee Infused with Red Ginger Water: A Hedonic Evaluation - I Made Dwi Andika Putra; I Wayan Muliana (HeadWay Research & Developemnt, 2025)
The increasing demand for innovative coffee beverages has encouraged the development of products that combine local agricultural commodities with functional ingredients. Pupuan Robusta coffee, one of Bali's premium local coffees, possesses distinctive sensory characteristics and offers potential for product innovation when combined with red ginger, a spice known for its unique flavour and bioactive properties. This study aimed to evaluate consumer acceptance of Pupuan Robusta coffee brewed with red ginger water using the V60 pour-over method through sensory evaluation. A quantitative descriptive research design was employed using a hedonic test involving 15 panelists, comprising three trained panelists and twelve semi-trained panelists. Six sensory attributes—bitterness, colour, acidity, aroma, body, and aftertaste—were assessed using a five-point hedonic scale. Data were analysed using descriptive statistics by calculating the mean score for each sensory attribute. The results indicated that the beverage achieved an overall mean score of 4.2, indicating that it was generally liked by the panelists. The highest acceptance was observed for colour, aroma, and aftertaste (mean = 4.4), while bitterness (3.9), acidity (4.2), and body (3.8) were also rated positively. These findings demonstrate that brewing Pupuan Robusta coffee with red ginger water using the V60 method produces a beverage with favourable sensory characteristics and high consumer acceptance. The study highlights the potential of integrating locally sourced coffee and herbal ingredients to develop innovative value-added beverages that support sustainable product diversification within Bali's coffee and hospitality industries.